Exploring meiofaunal assemblages in Pujada Bay, Philippines: A glimpse into one of the world's most beautiful bays - CIRILO O. YBAÑEZ JR. (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ybañez JR CO. 2024. Exploring meiofaunal assemblages in Pujada Bay, Philippines: A glimpse into one of the world's most beautiful bays. Biodiversitas 25: 1946-1954. This study explores the meiofaunal communities within Pujada Bay's intertidal zone, Philippines, meticulously recording 18,193 individuals across 18 taxa. Differences in composition and abundance across sites were observed, with conservation efforts at Guang-guang yielding higher densities (4,613 ind/10 cm-2) compared to less-managed sites such as Magsaysay (928 ind/10 cm-2) and Badas (1,438 ind/10 cm-2). Furthermore, Macambol, distant from direct threats, exhibited notable densities (4,483 ind/10 cm-2), indicating the importance of geographic isolation in ecosystem preservation. Dominant taxa include Nematoda (41%), Copepoda (28%), Foraminifera (22%), and Polychaeta (5%), underscoring their ecological significance in Pujada Bay's meiofaunal community. These findings highlight the efficacy of conservation measures in fostering resilient meiofaunal communities, where management strategies and geographic location play vital roles in biodiversity preservation. This research offers valuable insights into the ecological dynamics of Pujada Bay, emphasizing the indispensable role of conservation in maintaining biodiversity. By elucidating meiofaunal dynamics, this study advances our understanding of the local marine ecosystem and lays the groundwork for broader discussions on marine conservation strategies. Pujada Bay, considered one of the most beautiful bays in the world, exemplifies the delicate balance between human activities and the imperative of preserving biodiversity in marine environments.